English Language Textbooks at Government Schools in Nepal: Possibility of Cultivation and Promotion Creative Language Learning - Acharya, Tirtha Raj (Journal of Janta Multiple Campus, 2024)
The study is based on the analysis of English language textbooks at Government schools in Nepal. It is based on perceptions of English teachers teaching at Government schools in Morang district. Textbooks are materials prepared by Curriculum Development Centre (CDC) with the involvement of educators or subject experts to facilitate teaching-learning activities for achieving the goals of the curriculum. English language is being practiced as a Foreign Language through textbooks at Government school in Nepal. Moreover, English language textbooks have played a dual role in the context of Nepal. On the one hand, English textbooks have been teaching as a subject to overcome the examination, on the other hand, they have been using to create a real or real-like environment providing an ample opportunity of cultivation and promotion language learning to the learners of English. Textbooks are teaching-learning materials available in both forms hard copy and soft copy. The content coverage of English language textbooks seems to be effective to create better opportunities and promote a creative learning environment in the present context of Nepal.